Interleukin-10 regulates starvation-induced autophagy through the STAT3-mTOR-p70s6k axis in hepatic stellate cells. Issue 10 (May 2022) - Chen, Dongmei; Chen, Jiabing; Chen, Yizhen; Chen, Fenglin; Wang, Xiaozhong; Huang, Yuehong
The degree of activation of hepatic stellate cells (HSCs) is closely related to the level of autophagy in HSCs. We previously showed that interleukin-10 (IL-10) strongly inhibits HSC activation in rat fibrotic liver. However, little is known about the effect of IL-10 on HSC autophagy. For investigation of the effect of IL-10 on starvation-induced autophagy in immortal rat hepatic stellate cells (HSC-T6) and the molecular mechanism, HSC-T6 cells were incubated with serum-free DMEM for different periods and treated with IL-10 at different concentrations. Transmission electron microscopy (TEM), analysis of autophagic flux and Western blotting (WB) assays were used to observe changes in autophagosome morphology and number and autophagy-related protein expression in HSC-T6 cells and to evaluate the regulatory effect of IL-10 on starvation-induced autophagy. Cryptotanshinone (CPT) and rapamycin (Rapa) were used to block activation of the signal transducer and activator of transcription 3 (STAT3) and mTOR signaling pathways, respectively. STAT3-mTOR-p70s6k signaling pathway proteins were analyzed by WB to assess the signaling pathway by which IL-10 regulates autophagy. WB showed an increased LC3II/I ratio, increased Beclin1 expression, and decreased p62 expression in HSC-T6 cells starved for 3 h ( p < 0.05). IL-10 inhibited the increases in the LC3II/I ratio and Beclin1 expression and upregulated p62 expression ( p < 0.05), and the optimal IL-10 concentration was 20 ng/mL. TEM and double-labeled immunofluorescence analysis showed that IL-10 inhibited autophagosome formation and autophagic flux, as indicated by the decreased numbers of double-membrane autophagosomes and yellow autophagic puncta. Further examination of signaling pathway molecules showed that phosphorylation of the mTOR, STAT3, and p70s6k proteins was significantly decreased during starvation-induced autophagy, but IL-10 could increase mTOR, STAT3, and p70s6k protein phosphorylation ( p < 0.05). Blocking either the mTOR or STAT3 pathway reversed the inhibitory effect of IL-10 on starvation-induced autophagy in HSC-T6 cells ( p < 0.05). IL-10 suppresses starvation-induced autophagosome formation through activation of the STAT3-mTOR-p70s6k axis in HSC-T6 cells.